2008
DOI: 10.1149/1.2955726
|View full text |Cite
|
Sign up to set email alerts
|

Reactively Sputtered Mo–V Nitride Thin Films as Ternary Diffusion Barriers for Copper Metallization

Abstract: The effectiveness and performance of Mo-based ternary nitride films as copper diffusion barriers were investigated. Thermally stable Mo-V nitride thin diffusion barrier layers were deposited using radio frequency reactive magnetron sputtering and their barrier capability was evaluated and studied. Cu/Mo-V nitride/Si structures were fabricated and annealed at different temperatures. The agglomeration of Cu and the formation of Cu 3 Si due to high-temperature annealing were probed using scanning electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…The recent breakthrough in the chemical vapor deposition (CVD) growth of MoS 2 , WSe 2 , and WS 2 monolayers (Lee et al, 2012(Lee et al, , 2013Huang et al, 2014) has stimulated the direct growth of monolayer TMD alloys. Several recent manuscripts have shown that MoS 2x Se 2(1-x) is obtainable through the gas phase reaction of MoO 3 with the mixture of S and Se (Gong et al, 2013;Li et al, 2014;Mann et al, 2014). These preliminary works prove the theoretical prediction that TMD monolayer alloys are stable at room temperature (Jiang, 2012).…”
Section: Introductionsupporting
confidence: 56%
“…The recent breakthrough in the chemical vapor deposition (CVD) growth of MoS 2 , WSe 2 , and WS 2 monolayers (Lee et al, 2012(Lee et al, , 2013Huang et al, 2014) has stimulated the direct growth of monolayer TMD alloys. Several recent manuscripts have shown that MoS 2x Se 2(1-x) is obtainable through the gas phase reaction of MoO 3 with the mixture of S and Se (Gong et al, 2013;Li et al, 2014;Mann et al, 2014). These preliminary works prove the theoretical prediction that TMD monolayer alloys are stable at room temperature (Jiang, 2012).…”
Section: Introductionsupporting
confidence: 56%
“…The peaks at 232.5, 229.3, 163.4, and 162.2 eV can be assigned to the Mo 4+ 3d 3/2 , Mo 4+ 3d 5/2 , S 2– 2p 1/2 and S 2– 2p 3/2 , respectively. These XPS datum are in agreement with previous reports, further confirming that the three ion exchange processes are successfully completed.…”
supporting
confidence: 92%
“…Figure displays the detailed XPS scans for the Mo, S and Se binding energies for the as‐grown MoS 2 and those after selenization, where the magnitude of each profile was normalized for easier comparison. The as‐grown MoS 2 exhibits two characteristic peaks at 232.5 and 229.3 eV, attributed to the Mo 3d 3/2 and Mo 3d 5/2 binding energies for Mo 4+ . The peaks, corresponding to the S 2p 1/2 and S 2p 3/2 orbital of divalent sulfide ions (S 2− ) are observed at 163.3 and 162.1 eV .…”
mentioning
confidence: 99%